Chinese Business Law - Yu, Danling (Palgrave Macmillan, 2021)
1 Corporate Law; 2 Foreign Investment Law; 3 Securities Law; Appendix I: The Corporation Law of the People’s Republic of China (2013 Amendment) 135 Appendix II: The Law of the People’s Republic of China on Sino-foreign Equity Joint Ventures (2016 Amendment) 189 Appendix III: The Securities Law of the People’s Republic of China (2014 Amendment)